TRUE GRASP: Actors visualize and explore hidden limitations of an apparent win-win land management strategy in a MAB reserve. (July 2018) - Braasch, Marco; García-Barrios, Luis; Cortina-Villar, Sergio; Huber-Sannwald, Elisabeth; Ramírez-Marcial, Neptalí
Abstract: Win-win solutions might be short-lived. Government permission for smallholder farmers to extract and sell resin from a pine savanna biosphere-reserve in Mexico has settled a long dispute among different stakeholders in the short-term; however, forest production and conservation beyond 20 years are compromised due to low pine recruitment caused by competition with exotic grasses. Grass control practiced by farmers through grazing and fire has previously been discouraged by conservation authorities, which inadvertently limits long-term pine conservation and use. We describe the participatory design, rationale and simulation attributes of an educational, interactive, agent-based model that explores suites of management options and their economic and ecological outputs. We present and analyze the outcomes of four simulation workshops, where farmers and external-actors better grasped the complex ecological interactions involved in conserving and using pines in grazed pine savanna with exotic grasses, and discussed these findings with a long-term vision and tradeoff analysis approach. Highlights: Participatory multi-actor approach towards decision making. Agent-based modelling for long-term rural land use planning. Short-term benefits vs. long-term undesired regime shifts, how can we manage trade-offs?